(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2024)
In the Indonesian Civil Procedure Law there are principles regarding the regulation of Judicial Power, namely the principle of audi et alteram partem which means that the judge must listen to both parties in the case. The decision handed down by the judge in this case is a verstek decision. A verstek decision is a decision handed down by the court when one of the parties is not present at the hearing or does not respond after being summoned in an appropriate and legal manner. The judge, in using his authority, can issue a verstek decision without the presence of the defendant provided that the existing requirements are met, namely if the defendant has been legally and properly summoned by the court, but the defendant is not present at the trial and does not send his legal representative. This research aims to analyze verstek decisions that are detrimental to defendants in default cases, and focuses on matters regarding verstek decisions, starting from the conditions, legal remedies that can be taken if the judge hands down a verstek decision, as well as the execution of the decision if the losing party does not carry out court ruling. The methodology used in this research article is a normative-empirical legal research method, which examines positive law and applicable norms and statutory regulations. The research results show that the verstek decision in Supreme Court Decision Number 39/Pdt.G/2022/PN Cbd is very detrimental to the defendant, especially if the absence is caused by unavoidable factors. This raises the risk of injustice and potential abuse of the law by plaintiffs who may not have good intentions. Keywords: Verstek Decision, Defendant, Plaintiff, Resistance (Verzet), Execution.